Pengembangan Fitur Rekam Data Menggunakan Metode Multiple File (Studi Kasus Budidaya Jamur) - Aziz Maulana Rosyid; Eddy Nuraharjo (Universitas Sari Mutiara Indonesia Medan, 2022)
In the process of mushroom cultivation there are several things that must be considered, namely the factors that support the growth of mushrooms. The supporting factors that contribute to the growth of fungi are temperature conditions, humidity, air quality and light intensity. Based on the above conditions, this study aims to build a data recording feature to record the conditions of temperature, humidity, air quality and light intensity. With reference to the formulation of the problem, this study aims to develop a data record feature that later the data can be used by farmers to monitor the conditions of their cultivation sites or for further research. The method in this study using Multiple Files. The data recording feature will be carried out in real time using a Data Logger using Arduino Mega and additional sensors, including: DHT-22, MQ-135, LDR. From the resulting data retrieval, the feature has been running well. Data retrieval for 1 hour where data is taken every 10 minutes produces: The DHT-22 sensor shows an average temperature between 29.9 C and humidity of 74.8%. The LDR sensor shows a numerical value according to the light conditions in place, the brighter the light, the greater the value and vice versa. The MQ-135 sensor shows an average result of 117 PPM. This data record feature can help researchers and mushroom farmers who want to monitor the condition of their mushroom cultivation locations.